CAG Repeats in the androgen receptor gene is associated with oligozoospermia and teratozoospermia in infertile men in Jordan. (24th June 2020) - Al Zoubi, Mazhar Salim; Bataineh, Hamzah; Rashed, Mitri; Al‐Trad, Bahaa; Aljabali, Alaa A. A.; Al‐Zoubi, Raed M.; Al Hamad, Mohammad; Issam AbuAlArjah, Manal; Batiha, Osamah; Al‐Batayneh, Khalid M.
Abstract: CAG trinucleotide repeats are coded for the polyglutamine tract in the N‐terminal of the androgen receptor (AR) gene which varies in normal individuals from 6 to 36 residues. In this study, we inspected the impact of the CAG repeats on the spermatogenic defects by measuring the size of AR‐CAG repeats length in a cohort of 260infertile and 169 fertile Jordanian men. The infertile group included three subgroups of a zoospermic, oligozoospermic and teratozoospermia men. The CAG allele size was determined by direct sequencing. The results showed a significant association between the length of the AR‐CAG repeats and men's infertility ( p = .001). In particular, the current cohort demonstrated a significant association between the AR‐CAG length polymorphism and oligozoospermia ( p < .001) and teratozoospermia ( p < .001) but not azoospermia. According to distributions of allele frequency, the risk of oligozoospermia was 5.5‐fold greater than normal when alleles frequency > 20 repeats, while the risk of teratozoospermia was > 10.6 folds greater than normal when allele frequency > 22 repeats. In conclusion, our results underscored that the long repeats of the AR‐CAG polymorphism within the normal range might be associated with abnormal spermatogenesis such as teratozoospermia and oligozoospermia and contributing to infertility in Jordanian men.